2020
DOI: 10.1093/hmg/ddaa179
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for Alzheimer’s disease targeting CD33 reduces amyloid beta accumulation and neuroinflammation

Abstract: Neuroinflammation is a key contributor to the pathology of Alzheimer’s Disease (ad). CD33 (Siglec-3) is a transmembrane sialic acid-binding receptor on the surface of microglial cells. CD33 is upregulated on microglial cells from post-mortem ad patient brains and high levels of CD33 inhibit uptake and clearance of amyloid beta (Aβ) in microglial cell cultures. Furthermore, knock-out of CD33 reduces amyloid plaque burden in mouse models of ad. Here, we tested whether a gene therapy strategy to reduce CD33 on mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 61 publications
0
41
0
Order By: Relevance
“…Treatment of Alzheimer's disease mice with an adeno-associated virus (AAV) vector-based system encoding an artificial microRNA targeting CD33 (miR CD33 ) at an early age reduced CD33 mRNA, brain levels of TBS-soluble Aβ40 and Aβ42, and Aβ plaque burden in APP/PS1 mice. Early intervention with miR CD33 downregulated pro-inflammatory activation genes, cytokines and chemokines [ 63 ▪ ]. Collectively, we provided the first proof-of-concept that therapies targeting CD33 can reduce both Aβ accumulation and neuroinflammation.…”
Section: Alzheimer's Disease Risk Genes Cd33 and mentioning
confidence: 99%
“…Treatment of Alzheimer's disease mice with an adeno-associated virus (AAV) vector-based system encoding an artificial microRNA targeting CD33 (miR CD33 ) at an early age reduced CD33 mRNA, brain levels of TBS-soluble Aβ40 and Aβ42, and Aβ plaque burden in APP/PS1 mice. Early intervention with miR CD33 downregulated pro-inflammatory activation genes, cytokines and chemokines [ 63 ▪ ]. Collectively, we provided the first proof-of-concept that therapies targeting CD33 can reduce both Aβ accumulation and neuroinflammation.…”
Section: Alzheimer's Disease Risk Genes Cd33 and mentioning
confidence: 99%
“…For example, CD33 inactivation promoted the uptake of Aβ by microglia (Griciuc et al, 2013). Consistently, CD33 knockdown significantly decreased the proinflammatory-related transcripts and Aβ plaque in AD mice at an early age (Griciuc et al, 2020). Thus, CD33 might be a potential target for AD treatment.…”
Section: The Therapeutic Potential Of Targeting Microglia Polarizationmentioning
confidence: 75%
“…Consistently, the number of CD33-positive microglia markedly increased in the cortex of AD cases ( Griciuc et al, 2013 ). CD33 knockout led to the increase of inflammasome genes and anti-inflammatory gene expression in AD mice ( Griciuc et al, 2019 ), while a recent study further demonstrated that CD33 knockdown significantly decreased the pro-inflammatory-related transcripts in AD mice ( Griciuc et al, 2020 ; Figure 2 ).…”
Section: Dysregulation Of Microglia Polarization In Alzheimer’s Diseasementioning
confidence: 93%
“…CD33, a transmembrane sialic acid–binding receptor expressed on the surface of microglial cells, inhibits uptake and clearance of Abeta. ICV injection of an AAV vector encoding an artificial microRNA targeted against CD33 (miRCD33) in APP/PS1 mice reduced expression of pro-inflammatory genes (Tlr4, Il1b, Ccl2, and Tnfα) and amyloid beta accumulation ( Griciuc et al, 2020 ).…”
Section: Nbts In Orphan Neurological Disordersmentioning
confidence: 99%